2016
DOI: 10.1080/10412905.2016.1189856
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil composition and antioxidant activity in Valeriana jatamansi Jones: influence of seasons and growing sources

Abstract: d a G. B. Pant institute of himalayan Environment and Development, Kosi-Katarmal, almora, uttarakhand, india; b school of Environment and natural resources, Doon university, Dehradun; c Department of Botany, hamdard university (Jamia hamdard), new Delhi; d Guru Govind singh indraprastha university, Dwaraka, new Delhi ABSTRACTValeriana jatamansi is a perennial medicinal herb used in traditional and modern medicines for preventing number of diseases. Root samples were collected from wild and cultivated condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…In the mountainous region, variation in micro-climate is common, and this variation in uences the qualitative and quantitative parameters of medicinal and aromatic plants 48, 49,50 . The variations in essential oil concentrations in the wild populations and cultivated populations of V. jatamansi have also been reported earlier 31,36,44 . Despite proper agronomic practices, the oil concentration in the cultivated population (CSIR-IHBT) was lower than the populations from Kugti and Khani.…”
Section: Discussionsupporting
confidence: 73%
“…In the mountainous region, variation in micro-climate is common, and this variation in uences the qualitative and quantitative parameters of medicinal and aromatic plants 48, 49,50 . The variations in essential oil concentrations in the wild populations and cultivated populations of V. jatamansi have also been reported earlier 31,36,44 . Despite proper agronomic practices, the oil concentration in the cultivated population (CSIR-IHBT) was lower than the populations from Kugti and Khani.…”
Section: Discussionsupporting
confidence: 73%
“…Whereas antioxidant activity estimated using DPPH was higher in case of wild source. Comparative assessment revealed that essential oil exhibited stronger antioxidant activity than methanol extract (Rawat et al, ). Moreover, several molecular markers (intersimple sequence repeats markers) were also identified to be associated with the antioxidant activity of V. jatamansi measured by ABTS, DPPH, and FRAP assay, and their use in identification and breeding of quality plants was envisaged (Jugran, Bhatt, et al, ; Jugran et al, ).…”
Section: Medicinal Uses and Pharmacology Propertiesmentioning
confidence: 99%
“…Likewise Aspergillus fumigatus was found sensitive against hexane extract of the species at high concentration. However, methanolic extract of the species was found much effective against bacterial strains (Rawat et al, ).…”
Section: Medicinal Uses and Pharmacology Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Effectiveness of medicinal plants dependents upon amount of active constituents present in the species, which may be highly influenced by different factors such as, growing conditions, seasons, climatic conditions, sun light exposure, altitude, along with genetic make‐up etc . Therefore, selection of elite plants is essentially required, which contain higher phytochemical content and good pharmacological activity for obtaining maximum benefits.…”
Section: Future Prospective and Conclusionmentioning
confidence: 99%